Gestão de resíduos sólidos urbanos em Nossa Senhora da Glória : desafios à sustentabilidade socioambiental - Pereira, Alessandra Santana (2016)
The selective waste collect and environmental education have become important municipal solid waste management of the allies, the first returning to the production cycle materials that would otherwise go to disposal sites; and the second acting in raising awareness of social actors to be aware of the environmental problems faced by their community. This study aimed to analyze the management and the management of solid waste in the city of Nossa Senhora da Glória / SE. The methodology was based on the hypothetical-deductive method, opting for a descriptive, exploratory and quantitative and qualitative research. Data were collected through bibliographic and documentary sources; questionnaires from the teachers, students and servants of municipal schools Tiradentes, Presidente Tancredo Neves, Professor José Augusto Barreto and Antônio Francisco dos Santos. While the interviews with the Secretaries of Environment, Education and Social Action, in addition to the waste pickers. The mapping of points where there is solid waste disposal, location of the landfill (dump) the city and the mentioned schools still was made. With the social actors involved in the study we developed a Participatory Rapid Assessment. As one of the main results of this research highlights that the management of solid waste in the city considered the Capital of Sergipe Hinterland happen precariously and environmentally inadequate, as the safety equipment, treatment and final disposal, and verified the absence of selective collect. The collected waste is deposited in every place in the open, or directed to landfill. However, through visits to the study site was evident that the city has great potential in relation to recycling, for more than twenty families survive by selling this material, however, not all deposited recyclables in landfill is collected, losing a number of materials. It emphasizes the need for strengthening the solid waste policies within the municipality, to define and involve all sectors of society, from generation to final disposal. At the end of this work it was also proposed steps as a subsidy for Selective Collection Program based at the “Escola Municipal Presidente Tancredo Neves”, one of the four local schools that participated in this study.